PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP MELALUI MODEL PEMBELAJARAN SITUATION BASED LEARNING - Desi Rahmatika; Ali Syahbana; Yunika Lestaria Ningsih (Universitas Muhammadiyah Bengkulu, 2019)
ABSTRACTThis research aims to study enhancement of solving ability of student SMP Negeri 3 Muara Enim through Situation Based Learning (SBL) system. The method of this research is quasi experiment with pretest and posttest group design. Pupulation in this research that is all class VIII SMP N 3 Muara Enim, taken sample taken of two classed that class VIII.D many as 28 students as a class of experiment that get Situation Based Learning (SBL) system, and class VIII.C as much 29 students as a control class get conventional learning system. The instrument used in this study it test mathematical problem solving abilities in the form of essay questions that have been empirically validated. Data analysis uses N-Gain test and T test (Independent Sample t-Tes), with a prerequisite test first namely the test for normality and homogeneity. Based on the analysis of the data, the results obtained in this study stated that an increase in mathematical problem solving abilities of student of SMP Negeri 3 Muara Enim who obtained a Situation Based Learning (SBL) system was higher than students who received conventional learning. Keywords :Situation Based Learning (SBL), Mathematical Problem Solving Ability